2017
DOI: 10.1103/physrevb.95.235124
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic mass gap in uniaxially strained graphene

Abstract: We study the conditions for spontaneously generating an excitonic mass gap due to Coulomb interactions between anisotropic Dirac fermions in uniaxially strained graphene. The mass gap equation is realized as a self-consistent solution for the self-energy within the Hartree-Fock meanfield and static random phase approximations. It depends not only on momentum, due to the long-range nature of the interaction, but also on the velocity anisotropy caused by the presence of uniaxial strain. We solve the nonlinear in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 87 publications
2
21
1
Order By: Relevance
“…(2) previously derived by Barnes et al [25]. We note that according to Mishchenko 14 the numerical value of the two-loop coefficient is f ≈ −0.39 is reasonably close to the results of aforementioned calculations 14,17,23,25 . Note that recently Barnes et al 25 found that the three-loop coefficient f…”
Section: A Static Screening Approximationsupporting
confidence: 89%
See 2 more Smart Citations
“…(2) previously derived by Barnes et al [25]. We note that according to Mishchenko 14 the numerical value of the two-loop coefficient is f ≈ −0.39 is reasonably close to the results of aforementioned calculations 14,17,23,25 . Note that recently Barnes et al 25 found that the three-loop coefficient f…”
Section: A Static Screening Approximationsupporting
confidence: 89%
“…But certain characteristics of electron-electron interactions in graphene 7 still remain unsettled, as explained below, despite many sincere attempts to unravel the significance of interaction effects [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . An important manifestation of many-body interactions in freely suspended graphene was observed in the quasiparticle velocity, v(k), which was experimentally 22 shown to acquire a logarithmic enhancement close to one of its charge neutrality (Dirac) points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and 12) and the following valence bands: (5.14) and Note that n-fold degeneracy of bands ε 3 c and ε 3 v begins at n ≥ 2; and (n − 1)-fold degeneracy of bands ε 4 c and ε 4 v begins at n ≥ 3. For even number of layers, and stacking AA .…”
Section: The Tba Carrier Energy Band Structure Of the Multilayer Aa-smentioning
confidence: 99%
“…So far the previously reported expressions for truetruebold-italicυ¯, as a function on the strain tensor, have been derived without taking into account the effect of the relative displacement vector Δ . However, in order to gain more quantitative knowledge of the strain‐induced effects on graphene, such as optical transmittance modulation, asymmetric Klein tunneling or dynamical gap generation, it is required a precise relationship between strain and the fermion velocity anisotropy.…”
mentioning
confidence: 99%